Epidemiological and clinical characteristics of patients who died from Influenza A(H1N1)pdm09 in Viet Nam - Phan Thanh Tinh; Phan Trong Lan; Patel Mohamed; Tran Minh Nhu Nguyen (World Health Organization Regional Office for the Western Pacific, 2012)
We describe the epidemiological and clinical characteristics of patients who died from influenza A(H1N1)pdm09 in hospitals in Viet Nam between August 2009 and March 2010.Of 58 fatal cases, 32 (55%) were below 30 years of age and 14 (24%) were pregnant females. Forty-five (78%) patients had at least one underlying medical condition including chronic heart, kidney or lung diseases or pregnancy. Twelve (21%) cases sought medical attention on the day of symptom onset. Only 13 (36%) of 36 cases for whom treatment data were available had been given antiviral drugs within the recommended two days of symptom onset.The clinical and epidemiologic characteristics of the patients who died from influenza A(H1N1)pdm09 are similar to those reported from other countries. To improve preparedness and response to future pandemics, Viet Nam needs to strengthen the surveillance of influenza; increase laboratory capacity to test for influenza viruses; and develop strategies for promoting the timely attendance of at-risk individuals at health facilities and the early administration of antiviral drugs, particularly for persons with underlying medical conditions and pregnant females.